Pengaruh Status Kesehatan Rumah Terhadap Kejadian Tuberkulosis di Wilayah Kerja Puskesmas Sawangan - Rusman Efendi; Cindi Maduri; Thresya Febrianti; Siti Riptifah Tri Handari (Jurnal Kesehatan Indonesia, 2023)
Tuberculosis is an infectious disease that is a major cause of ill health and one of the leading causes of death worldwide. This study aims to analyze the effect of home health on the incidence of tuberculosis in the working area of the Sawangan Health Center, Depok. The design used is case control, to determine the effect of home health on the incidence of tuberculosis. The population in this study were the people in the working area of the Sawangan Public Health Center, Depok. The sample size was 60 respondents, consisting of 30 samples of tuberculosis sufferers and 30 samples as controls. Data were collected by observation, then the results of the study were analyzed using the chi-square test with univariate and bivariate analysis. The significance level uses ? 0.05. The results of the study found a significant effect of the ventilation area, lighting, and humidity of the house on the incidence of tuberculosis. There is no significant effect of the type of floor and the density of the house on the incidence of tuberculosis. The health condition of the house in general influences the incidence of tuberculosis, so that local health workers need to educate the public about creating housing conditions that meet health requirements.